Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/anie.200701782
|View full text |Cite
|
Sign up to set email alerts
|

FeCl2‐Catalyzed Selective CC Bond Formation by Oxidative Activation of a Benzylic CH Bond

Abstract: Any old iron: Readily available and nontoxic FeCl2 effectively catalyzes CC bond formation by oxidative activation of benzylic CH bonds in the presence of tert‐butyl peroxide as a stoichiometric oxidant (see scheme). The mild reaction conditions, good yields, low catalyst cost, and easy operation are the major advantages of this cross‐dehydrogenation coupling reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
75
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(77 citation statements)
references
References 29 publications
(3 reference statements)
1
75
0
1
Order By: Relevance
“…This chemistry is further explained by Masumi Itazaki and Hiroshi Nakazawa in [51]. Two notable examples of the reaction are shown in Scheme 3 [43,44]. Li pioneered the reaction catalyzed by iron in his work published in 2007 [43].…”
Section: C-c Bond-forming Reactionsmentioning
confidence: 93%
See 1 more Smart Citation
“…This chemistry is further explained by Masumi Itazaki and Hiroshi Nakazawa in [51]. Two notable examples of the reaction are shown in Scheme 3 [43,44]. Li pioneered the reaction catalyzed by iron in his work published in 2007 [43].…”
Section: C-c Bond-forming Reactionsmentioning
confidence: 93%
“…Two notable examples of the reaction are shown in Scheme 3 [43,44]. Li pioneered the reaction catalyzed by iron in his work published in 2007 [43]. The reaction typically proceeds under oxidative conditions, with tBuOOtBu, DDQ (2,3-dichloro-5,6-dicyano-1,4-benzoquinone), or K 2 S 2 O 8 commonly applied as oxidants.…”
Section: C-c Bond-forming Reactionsmentioning
confidence: 98%
“…In 2007, Li and coworkers reported the first example of selective CDC reaction of benzylic C-H bond catalyzed by iron salt FeCl 2 in the presence of t BuOO t Bu as the oxidant (Scheme 2) [8]. In this reaction, the catalytic activity of the iron salt was higher than those of Cu and Co salts.…”
Section: Introductionmentioning
confidence: 96%
“…The yield dramatically decreased by using an Iron-Catalyzed Cross-Dehydrogenative-Coupling Reactionsortho-substituted substrate (entry 7). Furthermore, substituted phenyls, naphthyl, seven-membered cyclic diphenyl methane derivatives, and isochroman were also adaptable to this reaction (entries 5,[8][9][10]. This catalytic system is also adaptable to the Mizoroki-Heck-type reaction of styrene with diphenylmethane, although the catalytic activity is low and substrate scope is limited (Scheme 18).…”
Section: Introductionmentioning
confidence: 96%
“…The benzylic C À H bond lacking an adjacent hetero-A C H T U N G T R E N N U N G atom is more difficult to activate; [14] however, Shi recently disclosed the use of DDQ for the arylation of diphenylmethane derivatives. [15] With this in mind, we began our study using the copper/indium system that we previously reported for the alkylation of benzylic ethers [16] but with DDQ as the oxidant in chlorobenzene (C 6 H 5 Cl).…”
mentioning
confidence: 99%